SOCIAL INTERACTIONS IN THE ASSYRIA FISHING POND - M Syukurman (Dinasti International Journal of Education Management And Social Science, 2019)
The purpose of this research was to describe the siocial interactions that occur in the Assyria fishing pond. This research done by qualitative research methods, which resulted in descriptive data. Therefore the key instruments was the researcher. The data sources were owners of ponds, pool guards, and anglers. Based on the results of data analysis, it was found: the form of social interaction that has been on the fishing pond of the Assyria family is associative social interactions and social interactions dissociative. Relationships that occur mutually supportive relationships, no disputes, converge in one fishing culture by not releasing their respective cultures. Competence and contraversi are still happening, but do not break the surface. The benefits that can be learned from the fishing of Assyria with the occurrence of soial interactions was the creation of patience, training optimism, and enjoying enjoyment, which can only be felt by anglers, how beautiful fishing. The lesson and wisdom that can be taken is that there was the philosophical business by having a high patience and attitude.